Electrical and Optical Properties of Carbon Nanotube Hybrid Zinc Oxide Nanocomposites Prepared by Ball Mill Technique - Guler, Omer; Guler, Seval Hale; Yo, Fahrettin; Aydin, Handan; Aydin, Cihat; El-Tantawy, Farid; Fouda, A. N. (Taylor & Francis Inc, 2015)
The electrical and optical properties of carbon nanotubes hybrid zinc oxide (ZnO-CNTs) nanocomposites synthesized by ball mill technique have been investigated. The nanocomposites were prepared using zinc oxide (ZnO) powder and carbon nanotube (CNT) synthesized by catalytic thermal chemical vapor deposition (CVD). The diameters and lengths of the CNTs were respectively determined to be 20-30 nm and about 3-5 mu m. DC conductivity measurements reveal that the nanocomposites are good conductive material. The room temperature DC electrical conductivity sigma(dc) of the un-doped ZnO and ZnO-CNT nanocomposites with 0.1% CNT, 0.5% CNT, and 1% CNT were found to be 6.55 x 10(-5), 5.46 x 10(-4), 1.49 x 10(-3), and 4.01 x 10(-3) S/cm, respectively. This indicates that there is a remarkable improvement of the electrical conductivity as the CNTs' content increases. The optical band gaps of the composites were determined by Kubelka-Munk theory based on the analysis of diffuse reflectance. The band gap (E-g) values of the composites decreased with increasing CNT contents. The obtained results indicate that the electrical and optical properties of ZnO semiconductor can be improved by incorporation of CNT.
Keywords: ZnO-CNTs hybrid; microstructure; electrical conductivity; optical properties